Case report: Autosomal recessive type 3 Stickler syndrome caused by compound heterozygous mutations in COL11A2 - Su, Ying; Ran, Chun-Qiong; Liu, Zhe-Long; Yang, Yan; Yuan, Gang; Hu, Shu-Hong; Yu, Xue-Feng; He, Wen-Tao (Frontiers in Genetics, 2023)
Background: Stickler syndrome (SS) is a group of hereditary collagenopathies caused by a variety of collagen and non-collagen genes. Affected patients have characteristic manifestations involving ophthalmic, articular, craniofacial and auditory disorders. SS is classified into several subtypes according to clinical and molecular features. Type 3 SS is an ultra-rare disease, known as non-ocular SS or otospondylomegaepiphyseal dysplasia (OSMED) with only a few pathogenic COL11A2 variants reported to date. Case presentation: A 29-year-old Chinese male was referred to our hospital for hearing loss and multiple joint pain. He presented a phenotype highly suggestive of OSMED, including progressive sensorineural deafness, spondyloepiphyseal dysplasia with large epiphyses, platyspondyly, degenerative osteoarthritis, and sunken nasal bridge. We detected compound heterozygous mutations in COL11A2, both of which were predicted to be splicing mutations. One is synonymous mutation c.3774C>T (p.Gly1258Gly) supposed to be a splice site mutation, the other is a novel intron mutation c.4750 + 5 G>A, which is a highly conservative site across several species. We also present a review of the current known pathogenic mutation spectrum of COL11A2 in patients with type 3 SS. Conclusion: Both synonymous extonic and intronic variants are easily overlooked by whole-exome sequencing. For patients with clinical manifestations suspected of SS syndrome, next-generation whole-genome sequencing is necessary for precision diagnosis and genetic counseling.